Manajemen Wisata Perdesaan Berdasarkan Tingkat Kepuasan Pengunjung di Tiga Desa Wisata di Bali - Oka Suryawardani, I Gusti Ayu (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
This research aims to analyse the level of visitor satisfaction in visiting rural tourism and management of rural tourism in Bali. Research was conducted in three rural tourism in Bali, namely Munduk, Jasri, and Pengelipuran from June to August 2019 through distributing questionnaires to 210 visitors. Data were analyzed based on quantitative approach by implementing the Importance Performance Analysis method. Results showed that the level of tourist satisfaction when visiting rural tourism in Bali was high in terms of attraction, hospitality, safety, and comfortability which indicated that performance of rural tourism has been in accordance with the expectation of tourists. However, the results showed that the level of tourist satisfaction is low in terms of cleanliness and health which indicated that the destination's performance does not match the expectations of tourists. Rural tourism management in Bali has been implemented holistically and comprehensively, however, implementation of marketing concept require some improvements.